The Influence of Social Media Usage Intensity on the Learning Motivation of Students in the Islamic Education Study Program - Sunoko, Ahmad; Fauzi, Moh Ali; Umar, Muallief; Nur Arafah, Nawal (STAI Miftahul Ula Nganjuk, 2025)
This study aims to analyze the effect of social media usage intensity on the learning motivation of students in the Islamic Education Study Program. A quantitative approach with a survey method was employed. The research population consisted of 150 students, with a sample of 109 respondents determined using Slovin’s formula at a 5% margin of error. The sampling technique applied was purposive sampling with the criterion of active students in at least their second semester. Data were collected using a Likert-scale questionnaire measuring two main variables: social media usage intensity (frequency, duration, and purpose) as the independent variable, and learning motivation (attention, relevance, confidence, and satisfaction) as the dependent variable. Instrument validity was tested using Pearson’s product–moment correlation, while reliability was assessed with Cronbach’s Alpha. Data analysis was conducted through simple linear regression with the assistance of SPSS software. The findings reveal that social media usage intensity has a positive and significant effect on students’ learning motivation, with a coefficient of determination (R²) of 0.192 or 19.2%. This indicates that social media contributes to enhancing learning motivation, although the majority of its variation (80.8%) is influenced by other factors beyond this study. These results support constructivist theory, the ARCS Motivation Model, and Self-Determination Theory, which emphasize the importance of interaction, relevance, and autonomy in fostering learning motivation. The findings are also consistent with previous studies confirming the pedagogical potential of social media in supporting learning, while simultaneously cautioning against its negative impacts when misused. Intensive and purposeful use of social media can serve as a supporting factor in enhancing students’ learning motivation, particularly in the Islamic Education Study Program, provided it is utilized wisely and integrated with other instructional strategies.